Connecticut River Atlantic Salmon Compact : report (to accompany H.R. 2062) (including cost estimate of the Congressional Budget Office). - United States. Congress. House. Committee on Resources. ([Washington, D.C. : U.S. G.P.O., 2001)
"November 8, 2001"--Pt. 1. Shipping list no.: 2002-0056-P (pt. 1). Distributed to some depository libraries in microfiche. Caption title. Mode of access: Internet.